2007
DOI: 10.1007/s10620-006-9086-4
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects of Aqueous Garlic Extract in Reducing Water Avoidance Stress-Induced Degeneration of the Stomach, Ileum, and Liver: Morphological and Biochemical Study

Abstract: We investigated the effect of aqueous garlic extract (AGE) on water avoidance stress (WAS)-induced degeneration of the gastric and ileal mucosa and liver parenchyma. Wistar albino rats were exposed to WAS (WAS group) for 5 days. After exposure of the animals to WAS, a 1 ml/kg aqueous garlic extract (AGE) was injected i.p. (WAS+AGE group). The stomach, ileum, and liver samples were investigated under light microscope for general morphology. Topography of gastric and ileal mucosa was investigated by scanning ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…Aged garlic extract and SAC in both vivo and cell culture-based previous studies recorded to preserve the levels of glutathione peroxidase and glutathione reductase, where glutathione reductase involved in conversion of oxidized glutathione to glutathione [52, 53]. Aged garlic extract treatment significantly prevented induced stress degeneration in morphology and reversed the increased level of MDA and the decreased GSH contents to control values of gastrointestinal mucosa due to its potent free radical scavenging and antioxidant properties [54]. The antioxidant properties of AGE ameliorated oxidative organ injury due to naphthalene toxicity by reversing significantly the elevated MDA levels and MPO activity levels [55].…”
Section: Discussionmentioning
confidence: 99%
“…Aged garlic extract and SAC in both vivo and cell culture-based previous studies recorded to preserve the levels of glutathione peroxidase and glutathione reductase, where glutathione reductase involved in conversion of oxidized glutathione to glutathione [52, 53]. Aged garlic extract treatment significantly prevented induced stress degeneration in morphology and reversed the increased level of MDA and the decreased GSH contents to control values of gastrointestinal mucosa due to its potent free radical scavenging and antioxidant properties [54]. The antioxidant properties of AGE ameliorated oxidative organ injury due to naphthalene toxicity by reversing significantly the elevated MDA levels and MPO activity levels [55].…”
Section: Discussionmentioning
confidence: 99%
“…In our experiment, we could not find significant difference in FCR between control and experimental groups. According to Zeybek et al (2007) medicinal plants protect the gastrointestinal tract from harmful bacteria which enhance the digestive enzymatic activities and that lead to high metabolic rate (FCR) and feed converted to meat. Lewis et al (2003) worked on a mixture of medicinal plants and found better FCR in broiler chicks throughout the experiment.…”
Section: Resultsmentioning
confidence: 99%
“…57 Supporting this speculation, we have previously shown that AGE administration reversed oxidant responses and improved tissue morphology and function in the stomach, ileum, liver, kidney, and bladder, while the reduced GSH levels were restored in all these tissues. 22,58,59 Similarly, renal GSH, SOD, and CAT levels that were decreased in cadmium-intoxicated rats were restored when rats were treated with garlic extract. 60 In many inflammatory disorders, important components of the pathological processes are linked to the ability of neutrophils to release several agents that can destroy normal cells and dissolve connective tissue.…”
Section: Discussionmentioning
confidence: 96%